IDENTIFIKASI Plasmodium vivax MENGGUNAKAN METODE NESTED PCR DI WILAYAH ENDEMIS MALARIA PROVINSI NUSA TENGGARA TIMUR - Dewi Inderiati; Sarwo Handayani; Danesya Syaeptiani; Ni Putu Aryadnyani (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2022)
East Nusa Tenggara Province has one of the highest malaria prevalence rates in Indonesia (1.99 percent) and is one of the locations where malaria is expected to be eradicated by 2030. There is a hypnozoite phase in P. vivax that might cause recurrence in patients. Only young erythrocytes are infected by P. vivax, resulting in a low parasite density in the blood. As a result, P. vivax is difficult to detect, necessitating the employment of an appropriate diagnostic procedure. With the advancement of molecular biology, it is now possible to diagnose malaria using the nested PCR method, resulting in more sensitive and specific results. The goal of this study was to identify P. vivax in 135 whole blood samples from people of Oenino District, South Central Timor Regency, East Nusa Teggara Province, using the nested PCR method. In this study, 8 (5.92%) of the samples tested positive for Plasmodium sp., with 5 (3.70%) of the samples being P. vivax. Patients with vivax malaria were mostly men (40.0%) and women (60.0%), with ages ranging from 31 to 50 years (40.0%), 41 to 50 years (20.0%), and > 50 years (20.0%). (40.0 % ). A total of three patients (40.0 %) experienced clinical signs of fever and anemia (20.0 %). Based on this results of a P. vivax examination, the PCR approach might be utilized. The discovery of P. vivax in the community needs o be concern for the local government, particularly in terms of malaria treatment monitoring and assessment in order to prevent relapse, increase malaria cases, and promote the effectiveness of malaria elimination initiatives.